Fifty Poems Fifty - Whittemore, Reed (Book collections on Project MUSE., 1970)
Fifty Poems Fifty was first published in 1970. In this, the seventh volume of his poetry to be published, Reed Whittemore presents fifty poems, all making their first appearance in book form here. Commenting on this collection, John Malcolm Brinnin writes: ""Whittemore has his own distinctive voice, his own spare, artfully simple way with a poem, and a grimly merry (or merrily grim) brand of wit that keeps a reader in a state of bemused expectation. His nonsense makes chilling good sense; and his poems inspired by affections are straightforward, touching, and without a twinge of sentimentality.